2018
DOI: 10.1051/matecconf/201815006036
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Radiation Effects on MHD with Flow Heat and Mass Transfer in Casson Nanofluid over A Stretching Sheet

Abstract: Abstract. The boundary layer heat and mass transfer flow of Casson nanofluid over a stretching sheet with constant wall temperature (CWT) under the magnetic field and thermal radiation effects is investigated numerically. Using similarity transformations, the governing equations are reduced to a set of nonlinear ordinary differential equations (ODEs). These equations are solved numerically by Shooting method. The effects of Casson parameter, magnetic parameter, porosity parameter, radiation parameter, Prandtl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Ganesh et al [21] studied numerically and analytically the impact of radiation over a horizontal stretching sheet on the flow of nanofluids. Dar [22] and Kho et al [23] analyzed numerically radiation effects in Casson nanofluid on MHD flow heat and mass transfer over a stretching sheet. Ullah et al [24] observed the radiation parameter and nanoparticles volumetric fraction are qualitatively similar for the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Ganesh et al [21] studied numerically and analytically the impact of radiation over a horizontal stretching sheet on the flow of nanofluids. Dar [22] and Kho et al [23] analyzed numerically radiation effects in Casson nanofluid on MHD flow heat and mass transfer over a stretching sheet. Ullah et al [24] observed the radiation parameter and nanoparticles volumetric fraction are qualitatively similar for the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the impact of increasing Hartman number resulted in the decrease of both local Nusselt and Sherwood numbers. Moreover, Kho et al 2 numerically inspected the limit layer warmth and mass transfer stream of Casson nanofluid over an extending sheet with constant wall temperature (CWT) under the magnetic field and warm radiation impacts. They reported that the limit layer thickness increment in temperature and concentration profiles nevertheless velocity profiles diminishes when Casson nanofluid parameter, magnetic parameter, and permeability parameter increment.…”
Section: Introductionmentioning
confidence: 99%
“…e inclusive references and in detail understanding on thermal radiation can be read in recent articles [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%